Peran Pendidikan Bahasa Indonesia dalam Memperkuat Identitas dan Kebudayaan Nasional di Era Global - Nur Laela Yuni Nursyariah Sumarlin; Amira Fadila Sari Siti Munawara; Nur Lija; Yohanes A Rutu Lengo; Yeremias Bardi (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to comprehensively analyze the role of Indonesian language education in strengthening national identity and culture amid the increasingly complex dynamics of globalization. Indonesian holds a strategic position as both the national and state language, functioning not only as a means of communication but also as a symbol of national unity, a marker of collective identity, and a medium for transmitting national cultural values. However, globalization—characterized by the dominance of foreign languages, particularly English, rapid digital transformation, and changing language attitudes among younger generations—poses serious challenges to the ideological and cultural functions of Indonesian, especially within formal education. This research employed a qualitative approach with a descriptive-analytical design. Data were collected through semi-structured interviews with teachers and students, classroom observations of Indonesian language learning practices, and document analysis of curricula and instructional materials at secondary and higher education levels. The data were analyzed thematically through data reduction, data display, and conclusion drawing, supported by source and technique triangulation to ensure the trustworthiness of the findings. The results indicate that Indonesian language education that integrates national values, literary texts, and cultural elements plays a significant role in fostering students’ awareness of national identity and positive attitudes toward the Indonesian language. Moreover, Indonesian language learning functions as a form of cultural practice that contributes to the preservation of national cultural values. Nevertheless, the study reveals challenges related to students’ pragmatic orientation toward global languages and the dominance of foreign languages in digital spaces. Therefore, strengthening Indonesian language education through integrative, contextual, and adaptive curricula and pedagogical practices is essential to address global challenges while sustaining Indonesia’s national identity and cultural continuity.